Antioxidant, Thrombolytic and Cytotoxic Activities of Picrasma javanica (Dhaka University Journal of Pharmaceutical Sciences, 2012)
The methanol extract of leaf of Picrasma javanica as well as its n-hexane, carbon tetrachloride,chloroform and aqueous soluble partitionates were subjected to screening for antioxidant and thrombolytic activities and brine shrimp lethality. The antioxidant potential was evaluated by DPPH, Folin-Ciocalteau reagent and phosphomolybdenum total antioxidant assays using butylatedhydroxytolune (BHT) and ascorbic acid as standards. All fractions showed moderate to strong antioxidant activity, of which the chloroform and aqueous soluble fractions demonstrated the highest activity with the IC50 value of 14.59 ± 0.73 ?g/ml and 18.6 ± 0.15 ?g/ml, respectively. The  total phenolic content of the chloroform and aqueous soluble fractions was 10.4 ± 0.64 and 5.15 ± 0.22 mg of GAE/g of extractive, respectively. Thus, a positive correlation was found between the total phenolic content and total antioxidant activity of P. javanica. The general toxicity was determined by brine shrimp lethality bioassay where the crude extract (LC50 1.04 ± 0.31 ?g/ml) and its n-hexane (LC50 1.28 ± 0.45?g/ml) soluble partitionate demonstrated the  presence of considerable bioactive principles. Mild to moderate thrombolytic activity was discerned by the methanol extract of leaf of P. javanica and its different fractions. During assay for thrombolytic activity, the carbon tetrachloride soluble materials revealed 34.165±1.57 % of clot lysis while standard streptokinase and water, used as positive and negative controls, demonstrated 66.77% and 3.791% lysis of clot, respectively. DOI: http://dx.doi.org/10.3329/dujps.v11i1.12491 Dhaka Univ. J. Pharm. Sci. 11(1): 71-74, 2012 (June)